Dermal Delivery Enhancement of Natural Anti-Ageing Compounds from Ocimum sanctum Linn. Extract by Nanostructured Lipid Carriers - Wantida Chaiyana; Songyot Anuchapreeda; Suvimol Somwongin; Pachabadee Marsup; Kuan-Han Lee; Wei-Chao Lin; Shang-Chian Lue (MDPI AG, 2020)
This study aimed to develop nanodelivery systems for enhancing the Ocimum sanctum Linn. extract delivery into the skin. Rosmarinic acid (RA) was used as a marker for the quantitative determination of the extract by high-performance liquid chromatography. Nanostructured lipid carriers (NLC), nanoemulsion, liposome, and niosome, were developed and characterized for internal droplet size, polydispersity index (PDI), and zeta potential using photon correlation spectroscopy. Irritation properties of each formulations were investigated by hen's egg test on the chorioallantoic membrane. In vitro release, skin permeation, and skin retention are determined. NLC was suggested as the most suitable system since it enhances the dermal delivery of RA with the significant skin retention amount of 27.1 ± 1.8% (p < 0.05). Its internal droplet size, PDI, and zeta potential were 261.0 ± 5.3 nm, 0.216 ± 0.042, and −45.4 ± 2.4 mV, respectively. RA released from NLC with a sustained release pattern with the release amount of 1.29 ± 0.15% after 24 h. NLC induced no irritation and did not permeate through the skin. Therefore, NLC containing O. sanctum extract was an attractive dermal delivery system that was safe and enhanced dermal delivery of RA. It was suggested for further used as topical anti-ageing products.